Urban child health: does parent characteristics matter? - Ismail, Normaz Wana; Sivadas, Sudha; Said, Rusmawati; Abd Rahman, Azmawani (Springer, 2021)
Lifestyle changes due to urbanization in Malaysia are increasingly pronounced. Although only an upper middle-income country, obesity levels among Malaysian children were comparable to children from high-income countries. Hence, this paper aims to investigate the prevalence of obesity among children, including the impact of urbanization and parental socio-demographic background that contribute to its rise. Using secondary data from the Malaysian National Health and Morbidity Survey, we explore factors that contribute to the rising prevalence of overweight and obese children by employing the multinomial probit regression. These surveys are cross-sectional population studies, involving approximately between 30,000 and 56,000 respondents with a response rate above 84%. Findings show overweight and obesity prevalence in urban areas are influenced by the various demographic, socioeconomic and lifestyle-related factors. This study find that urban children are 1.7% less overweight while obesity increased by 20% between 2006 and 2015. In term of parent’s characteristics, parent education does not seem to have an impact as children from households headed by those without formal education record higher prevalence. In summary, factors that influenced urban children to become overweight in 2006 still persists after a decade.